RELEVANSI ISLAMIC WORLDVIEW DENGAN PARADIGMA PEMIKIRAN THOMAS KUHN - Fitri Ramadhani (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This study aims to elaborate on the concept of Thomas Kuhn's paradigm of thought and Islamic Worldview. Discusses the characteristics of Thomas Kuhn's scientific revolution paradigm and its relevance to the Islamic Worldview. This research is descriptive research that uses a qualitative approach through library research data collection methods. The data that has been collected is used as a source of information to be analyzed in this study. There are similarities and relevance between Thomas Kuhn's paradigm of thought and the Islamic Worldview. Thomas Kuhn's paradigm of thought is divided into a metaphysical paradigm, a sociological paradigm, and a construct paradigm, while its relevance in the Islamic Worldview is the epistemology of Bayani, Burhani, and Irfan. As well as the concept of incommensurable which is in line with ijtihad.Keywords: Paradigm of Thought; Islamic Epistemology; Islamic Worldview